Pembuatan Effervescent Kopi Robusta Hijau (Coffee robusta) dengan Campuran Bubuk Bji Alpukat (Persea americana Mill) sebagai Minuman Instan Fungsional - Apriliantika, Sugy Dwi; Priyanto, Gatot (Seminar Nasional Lahan Suboptimal, 2023)
Apriliantika, S.D., & Priyanto, G. (2023). The effervescent green robusta coffee (Coffea robusta) making with powdered avocado beans (Persea americana Mill) as instant functional beverages. In: herlinda S et al. (Eds.), Prosiding Sminar Nasional Lahan Suboptional ke-11 tahun 2023, Palembang 21 Oktober 2023. (pp. 447-463). Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Functional instant drinks containing antioxidants are booming among the public, but most of them still require a stirring process so they need to be converted into effervescent tablets to speed up dissolution. This research aimed to determine the selected formulations and the addition of avocado seed powder and green robusta coffee powder to the physical, chemical and organoleptic characteristics of effervescent tablets. This study used a Completely Randomized Design (RAL) Factorial with 12 level of treatment and each was repeated 3 times.  Treatment factors included the addition of avocado seed powder ( A1 = 20 % b/b; A2 = 15 % b/b; A3 = 10 % b/b; A4 = 0 % ) b/b) and robusta coffee powder green ( B1 = 0 %; B2 = 10 %; B3 = 20 % ). This results showed that the addition of avocado seed powder and green robusta coffee powder had a significant effect of antioxidant activity, water content, soluble time, hardness, and organoleptic.  Based on the results of the study, it was that the treatment of choice for effervescent tablets was the A3B2 treatment (10 % avocado seed powder ; 10 % green robusta coffee powder) from sensory test results with an average value of antioxidant activity (IC50) of 63,12 ppm, water content 4,34 %, hardness 110,096 kgf, soluble time 1,39 minutes, color sensory characteristics 6,47, aroma 6,2 and taste 5,87.